The emergence of lncRNAs in cancer biology - Prensner, John R. (2011)
The discovery of numerous non-coding RNA (ncRNA) transcripts in species from yeast to mammals has dramatically altered our understanding of cell biology, especially disease biology such as cancer. In humans, the identification of abundant long ncRNA (lncRNAs) >200 bp in length has catalyzed their characterization as critical components of cancer biology. Recently, roles for lncRNAs as drivers of tumor suppressive and oncogenic functions have appeared in prevalent cancer types, such as breast and prostate cancer. In this review, we will highlight the emerging impact of ncRNAs in cancer research, with a particular focus on the mechanisms and functions of lncRNAs.